7.8k views
3 votes
Solve the initial-value problem: y" - 4y' + 8y = 0, y(0) = 1, y'(0) = 2.

User Tsung Wu
by
5.8k points

1 Answer

2 votes

Answer:

The solution of the problem is
y(t) = e^(2 t) cos(2 t)

Explanation:

First we will write the characteristic equation which is


x^(2) -4x + 8 = 0

Now, we will solve this quadratic equation using the general formula.

Given a quadratic equation of the form,
ax^(2) +bx +c = 0, then

From the general formula,


x = \frac{-b+\sqrt{b^(2)-4ac } }{2a} or
x = \frac{-b-\sqrt{b^(2)-4ac } }{2a}

From the characteristic equation,
a = 1, b = -4, and
c = 8

Hence,


x = \frac{-(-4)+\sqrt{(-4)^(2)-4(1)(8) } }{2(1)} or
x = \frac{-(-4)-\sqrt{(-4)^(2)-4(1)(8) } }{2(1)}


x = (4+√(-16) )/(2) or
x = (4-√(-16) )/(2)


x = (2+4i )/(2) or
x = (2-4i )/(2)


x = 2 + 2i or
x = 2 - 2i

That is,
x =
2 ±
2i

Then,
x_(1) = 2 + 2i and
x_(2) = 2 - 2i

These are the roots of the characteristic equation

The roots of the characteristic equation are complex, that is, in the form

(
\alpha ±
\beta i).

For the general solution,

If the roots of a characteristic equation are in the form (
\alpha ±
\beta i), the general solution is given by


y(t) = C_(1)e^(\alpha t) cos(\beta t) + C_(2)e^(\alpha t) sin(\beta t)

From the characteristic equation,


\alpha = 2 and
\beta = 2

Then, the general solution becomes


y(t) = C_(1)e^(2 t) cos(2 t) + C_(2)e^(2 t) sin(2t)

Now, we will determine
y'(t)


y'(t) = 2C_(1)e^(2 t) cos(2 t) - 2C_(1)e^(2t)sin(2t) + 2C_(2) e^(2t)sin(2t) +2C_(2)e^(2t)cos(2t)

From the question,

y(0) = 1

and

y'(0) = 2

Then,


1 = y(0) = C_(1)e^(2 (0)) cos(2 (0)) + C_(2)e^(2 (0)) sin(2(0))


1 = C_(1)e^( 0) cos(0) + C_(2)e^(0) sin(0)

(NOTE:
e^(0) = 1, cos(0) = 1 and
sin(0) = 0 )

Then,


1 = C_(1)


C_(1) = 1

Also,


2 = y'(0) = 2C_(1)e^(2 (0)) cos(2 (0)) - 2C_(1)e^(2(0))sin(2(0)) + 2C_(2) e^(2(0))sin(2(0)) +2C_(2)e^(2(0))cos(2(0))
2 = 2C_(1)e^(0) cos(0) - 2C_(1)e^(0)sin(0) + 2C_(2) e^(0)sin(0) +2C_(2)e^(0)cos(0)


2 = 2C_(1) +2C_(2)

Then,


1 = C_(1) +C_(2)


C_(2) = 1 - C_(1)

Recall,
C_(1) = 1


C_(2) = 1 - 1 = 0


C_(2) = 0

Hence, the solution becomes


y(t) = e^(2 t) cos(2 t)

User Taynguyen
by
5.5k points